ESG and Firm Value (Study on Energy Sector Companies Listed on the Indonesia Stock Exchange) - Nilmawati Nilmawati; Gabriel Reinhard Sitindaon; Sri Budiwati Wahyu Suprapti (AIBPM Publisher, 2025)
The purpose of this study is to look into how firm value in energy businesses listed on the Indonesia Stock Exchange is affected by environmental, social, and governance disclosures. Tobin's Q and the cost of capital are used to calculate firm value. Using energy firms listed on the Indonesia Stock Exchange between 2021 and 2023, this study employs a quantitative method utilizing a multiple regression approach. The sample companies are those who use the GRI Standards in their sustainability reports to provide environmental, social, and governance information. With a total of 63 observations, the sample size that results is 21 firms. The findings indicate that social and governance factors have no bearing on company value, on the other hand, environmental considerations considerably raise Tobin's Q and lower the cost of capital. Investors can evaluate businesses using non-financial data thanks to these discoveries. Firm value may be impacted by non-financial disclosure, such as environmental factors in this instance.